Effectiveness of Preservation Methods on Quality of Mangrove Crab (Scylla serrata) - Napitupulu, S.St.Pi, M.Sc, Romauli Juliana; Sipahutar, Yuliati H (Politeknik Kelautan dan Perikanan Karawang, 2023)
Mangrove crab (Scylla serrata) was one of the fisheries export commodities and also got high demand in traditional markets, mini markets, and supermarkets. Inadequate storage and inappropriate handling during processing lead to decreasing weight and quality of mangrove crabs. The present study aims to investigate the effectiveness of different preservation methods of mangrove crabs on quality and physicochemicals to inhibit quality deterioration. The preservation methods are cold, frozen, and live and the period of storage is between 0, 2, 5, 8, and 12 days. The obtained result showed that frozen storage is longer than cold and lived storage to maintain quality (organoleptic, moisture level, TVB, and pH). Mangrove crabs are kept alive is better than frozen and cold storage to maintain weight loss.